2018
DOI: 10.1093/geront/gny137
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Informal Caregiving for Older Adults on the Health of Various Types of Caregivers: A Systematic Review

Abstract: ObjectiveInformal care, the provision of unpaid care to dependent friends or family members, is often associated with physical and mental health effects. As some individuals are more likely to provide caregiving tasks than others, estimating the causal impact of caregiving is difficult. This systematic literature review provides an overview of all studies aimed at estimating the causal effect of informal caregiving on the health of various subgroups of caregivers.MethodologyA structured literature search, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
275
1
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(304 citation statements)
references
References 37 publications
17
275
1
11
Order By: Relevance
“…Despite these results, recent literature reviews have shown the negative health impact of providing informal care [ 11 , 12 ]. A systematic review covering studies from various continents/countries (Europe, Asia, United States and Australia) highlights the negative impact of caregiving on the mental and physical health of the informal caregiver, especially female, married caregivers and those providing intensive care [ 11 ]. Cottagiri and Sykes [ 12 ] stress musculoskeletal disorders and psychological issues (such as depression, stress and anxiety) as the main health impacts of providing informal care.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these results, recent literature reviews have shown the negative health impact of providing informal care [ 11 , 12 ]. A systematic review covering studies from various continents/countries (Europe, Asia, United States and Australia) highlights the negative impact of caregiving on the mental and physical health of the informal caregiver, especially female, married caregivers and those providing intensive care [ 11 ]. Cottagiri and Sykes [ 12 ] stress musculoskeletal disorders and psychological issues (such as depression, stress and anxiety) as the main health impacts of providing informal care.…”
Section: Introductionmentioning
confidence: 99%
“…Por lo general, los cuidadores informales no reciben remuneración económica por esta tarea 4 , ni tampoco cuentan con la formación para los diferentes cuidados que proveen 5 . Así, el cuida-do puede llegar a convertirse en una tarea muy exigente, provocando tensión física, fatiga, desgaste emocional o estrés 6,7 , lo que en situaciones extremas puede dar paso al llamado "síndrome del cuidador", donde el individuo se siente incapaz de afrontar todas las responsabilidades que le exige el cuidado, llegando a una situación de sobrecarga que compromete su bienestar, y que puede desencadenar alteraciones en su salud física y emocional 8 .…”
unclassified
“…En esta línea, varios son los estudios que se han realizado para determinar si proveer cuidado informal se asocia negativamente con la salud tanto física como mental del cuidador, lo cual ha sido ampliamente confirmado por varios de estos estudios, destacando algunas revisiones sistemáticas y metaanálisis efectuados 6,9,10 . En el caso particular de América Latina, si bien la evidencia existente es aún escasa, esta también sugiere que el cuidado compromete la salud de quien cuida 5,[11][12][13][14] .…”
unclassified
See 1 more Smart Citation
“…However, we know that family members providing care to those with long-term chronic or terminal conditions can experience physical, emotional, social and financial distress, as well as short-and long-term health impacts (Bom, Bakx, Schut, & Doorslaer, 2018;Cameron, Franche, Cheung, & Stewart, 2002;Grande, Farquhar, Barclay, & Todd, 2004;Keating & Eales, 2017;Zarit, 2004). Their abilities to control the impact of care provision on their health can be limited once they make the commitment to care, especially when client symptoms are complex, other supports are lacking, or carers have additional family or employment responsibilities.…”
mentioning
confidence: 99%